1992
DOI: 10.1021/j100196a046
|View full text |Cite
|
Sign up to set email alerts
|

Fluid dinitrogen tetroxide at very high pressure and high temperature: observation of the nitrite isomer

Abstract: components must refer to N2/Rh/Ti02.Although the integrated area for the N2 band in the 2250-cm-' region of Figure 9 was lower in each spectrum at a given pressure than was its analog in Figure 1, a Langmuir isotherm fit from the band area data in Figure 9 provided an adsorption equilibrium constant of 0.541 atm-i. This was significantly higher than the value (0.376 obtained from the data of ~i~~~~ 1. This indicata that the =avst r e d u d near SMSI -&tions J. Phys. Chem. 1992, 96, 7092-7096 the N2 infrared ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 0 publications
2
27
1
Order By: Relevance
“…Self oxidation of NO at 79±80 K gives a red solid which is described by its IR spectrum as NO + NO 3 ± , and which also has been observed by warming of one of the two (syn and anti) isomers of ON±O±NO 2 [6,7]. Both ON±O±NO 2 and NO + NO 3 ± have been also observed by vibrational spectroscopy at high pressure [8,9]. Furthermore it is assumed that weak electron donor solvents will form adducts of the type D → N 2 O 4 , whereas strong electron donor solvents will stabilize the ionic form NO + NO 3 ± [10].…”
Section: Introductionmentioning
confidence: 93%
“…Self oxidation of NO at 79±80 K gives a red solid which is described by its IR spectrum as NO + NO 3 ± , and which also has been observed by warming of one of the two (syn and anti) isomers of ON±O±NO 2 [6,7]. Both ON±O±NO 2 and NO + NO 3 ± have been also observed by vibrational spectroscopy at high pressure [8,9]. Furthermore it is assumed that weak electron donor solvents will form adducts of the type D → N 2 O 4 , whereas strong electron donor solvents will stabilize the ionic form NO + NO 3 ± [10].…”
Section: Introductionmentioning
confidence: 93%
“…60 The reaction of nitrogen dioxide with alkenes is also made complex by virtue of the delicate equilibrium that exists between this compound, dinitrogen tetroxide (N 2 O 4 ; 28 ) 61 and its nitrite isomer 26 (Scheme 1). 62 Furthermore, in polar media, both 26 and 28 can undergo heterolytic dissociation to form nitrosonium-nitrate ( 29 ) and nitronium-nitrite ( 30 ) ion pairs, which can also participate in the addition process. 63 As a consequence, reactions of N 2 O 4 -NO 2 with alkenes are often complex, display significant solvent effects and lead to the formation of numerous products, as exemplified by 2,3-dimethyl-2-butene ( 31 ) (Scheme 2).…”
Section: Binary Nitrogen Oxides and Related Reagentsmentioning
confidence: 99%
“…Nitrogen dioxide (NO 2 ) is notoriously known to self associate in the liquid phase to produce dinitrogen tetroxide (N 2 O 4 ) according to Equation 1 [8]. In the liquid phase, N 2 O 4 can also additionally isomerizes [22]. In the vapor phase, it was shown that dimerization also occurs, while the formation of trimers, tetramers or sequential indefinite self-association hypothesis can be discarded [23].…”
Section: Introductionmentioning
confidence: 99%